Upaya Meningkatkan Pengetahuan Kelompok Lansia dengan DM di Desa Langkap Kecamatan Kedungwuni Kabupaten Pekalongan - Dwi Fijianto; Herni Rejeki; Tri Sakti Wirotomo; Jamaludin Yusuf; Firman Faradisi (Universitas Serang Raya, 2024)
One of the threats of degenerative diseases to public health is diabetes. Diabetes Mellitus (DM) is a chronic disease that occurs because the pancreas does not produce enough insulin or the body does not effectively use insulin. The prevalence of diabetes in the world in 2000 was 2.8% and it is predicted to increase to 4.4% in 2030. The purpose of this activity is to provide education to elderly groups with DM. The implementation of the activity begins with screening activities for elderly people who suffer from DM, found as many as 18 people with DM. Implementation of health education is given to the DM elderly group by providing material about DM disease and its treatment using the lecture-discussion method accompanied by a demonstration for 75 minutes. The results of the service showed that the participants' knowledge of diabetes mellitus increased from 6.56 to 8.22. The DM health education program for the elderly group of people with DM has been implemented and provides benefits for elderly people with DM so that they can improve their health